The influence of tualang honey in tensile strength and microscopic aspect (fibroblast and epithelization) of laparatomy wound healing in malnourished rabbits - Zaharudin, Ismazizi (2010)
Based on published reports that honey accelerates wound healing, an investigation on its role in laparotomy wound healing in term of tensile strength and microscopic aspect (fibroblast and epithelialization) on malnourished rabbits was carried out. Forty six female New Zealand white rabbits at the age of 6 weeks, weighing about 2 to 3 kg had a 4 centimeter infraumbilical laparatomy wound inflicted on their abdomen. They were divided into three groups which were malnourished group treated with topical and oral used of honey, malnourished and well-nourished group treated with topical and oral used of normal saline. Wound dressing was done every day and any changes over the wound were documented. The mechanical strength and histopathological examination were more favorable toward the malnourished group treated with topical and oral used ofTualang honey. The malnourished group treated with topical and oral used Tualang honey displayed a better tensile strength result compared to malnourished and well-nourished group treated with topical and oral used of normal saline at day 7 and 14 ( P<0.05 ) . For histopathological examination, both parameter epithelial and fibroblast count were also favorable towards the malnourished group treated with topical and oral used Tualang honey. The epithelial and fibroblast count were better in the malnourished group treated with the topical and oral used Tualang honey compared to malnourished and well-nourished group treated with topical and oral used of normal saline at day 7 and day 14 ( P<0.05 ). However, there were no significant difference in epithelial count for the malnourished group treated with topical and oral used Tualang honey compared to well-nourished group treated with topical nad oral used normal saline in day 14 ( P>0.05 ). Our study suggest that oral and topical Tualang honey dressing enhances the laparotomy wound healing in malnourished rabbits by increasing the numbers of fibroblast and epithelial cells which lead to increased wound strength.